2020
DOI: 10.1101/2020.01.20.913111
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial receptive field structure of double-opponent cells in macaque V1

Abstract: Double-opponent (DO) cells are well-suited to contribute to the spatial processing of color due to their spatially opponent and cone-opponent receptive fields (RFs).However, the representation of visual images by DO cells in monkey primary visual cortex is unclear because the spatial RF structure of DO cells has not been fully characterized. Early reports suggested that DO cells have center-surround RFs, but more recent studies have shown that some DO cells are orientation-tuned. To characterize the RFs of DO … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 75 publications
1
5
0
Order By: Relevance
“…Whether real V1 neurons respond in accordance with the energy model or show enhanced responses to natural alignments between chromatic and luminance signals is an important and unanswered question.In summary, DO cells and simple cells have much in common. As shown by the current study, both cell types combine signals roughly linearly across their RFs and, as shown previously, they share a Gabor-like RF structure(De and Horwitz, 2020). These observations motivate the idea that simple cells and DO cells are closely related neuronal types that may contribute similarly to downstream circuits that integrate coneopponent and cone-non-opponent signals for spatial image analysis.…”
supporting
confidence: 87%
See 4 more Smart Citations
“…Whether real V1 neurons respond in accordance with the energy model or show enhanced responses to natural alignments between chromatic and luminance signals is an important and unanswered question.In summary, DO cells and simple cells have much in common. As shown by the current study, both cell types combine signals roughly linearly across their RFs and, as shown previously, they share a Gabor-like RF structure(De and Horwitz, 2020). These observations motivate the idea that simple cells and DO cells are closely related neuronal types that may contribute similarly to downstream circuits that integrate coneopponent and cone-non-opponent signals for spatial image analysis.…”
supporting
confidence: 87%
“…By definition, simple cells have large, non-opponent L- and M-cone weights, and DO cells have cone-opponent weights. We used the same cone weight criteria that we used previously to facilitate comparison between studies (De and Horwitz, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations